Polymorphisms of TNF-alpha (− 308), IL-1beta (+ 3954) and IL1-Ra (VNTR) are associated to severe stage of endometriosis in Mexican women: a case control study - Jennifer Mier-Cabrera; Oliver Cruz-Orozco; Julio de la Jara-Díaz; Oscar Galicia-Castillo; Mario Buenrostro-Jáuregui; Alicia Parra-Carriedo; César Hernández-Guerrero (BMC, 2022)
Abstract Background Endometriosis is an estrogen-dependent and chronic inflammatory disease affecting up to 10% of women. It is the result of a combined interaction of genetic, epigenetic, environmental, lifestyle, reproductive and local inflammatory factors. In this study, we investigated whether single nucleotide polymorphisms (SNPs) mapping to TNF-alpha (TNF, rs1800629) and IL-1beta (IL1B, rs1143634) and variable number tandem repeat polymorphism mapping to IL1-Ra (IL1RN intron 2, rs2234663) genetic loci are associated with risk for endometriosis in a Mexican mestizo population. Methods This study included 183 women with confirmed endometriosis (ENDO) diagnosed after surgical laparoscopy and 186 women with satisfied parity and without endometriosis as controls (CTR). PCR/RFLP technique was used for genotyping SNPs (rs1800629 and rs1143634); PCR for genotyping rs2234663. Results We found no statistical differences in age between groups nor among stages of endometriosis and the CTR group. We observed no difference in genotype and allele frequencies, nor carriage rate between groups in none of the three studied polymorphisms. The prevalence of TNF*2-allele heterozygotes (p = 0.025; OR 3.8), TNF*2-allele (p = 0.029; OR 3.4), IL1B*2-allele heterozygotes (p = 0.044; OR 2.69) and its carriage rate (p = 0.041; OR 2.64) in endometriosis stage IV was higher than the CTR group. Surprisingly, the carriage rate of IL1RN*2-allele (ENDO: p = 0.0004; OR 0.4; stage I: p = 0.002, OR 0.38; stage II: p = 0.002, OR 0.35; stage III: p = 0.003, OR 0.33), as well as the IL1RN*2-allele frequencies (ENDO: p = 0.0008, OR 0.55; I: p = 0.037, OR 0.60; II: p = 0.002, OR 0.41; III: p = 0.003, OR 0.38) were lower than the CTR group. Women with endometriosis stage IV (severe) had frequencies more alike to the CTR group in the IL1RN*2 allele frequency (31.2% vs. 27.2%) and carriage rate (37.5% vs. 41.9%). Conclusion Although these polymorphisms are not associated with the risk of endometriosis, Mexican mestizo women with severe stage of endometriosis have higher frequencies of TNF*2-, IL1B*2- and IL1RN*2-alleles, which may explain a possible correlation with disease severity rather than predisposition or risk.